2022
DOI: 10.1111/and.14589
|View full text |Cite
|
Sign up to set email alerts
|

A review on applications and toxicities of metallic nanoparticles in mammalian semen biology

Abstract: The advent of nanotechnology since the 1950s, when the well‐known physicist Richard P. Feynman talked in his famous talk about “There's plenty of room at the bottom”, has led to incredible contribution of nanotechnology in the fields of medical and veterinary therapeutics, diagnostics and other applications. Semen biology dealing with the study of spermatozoa and its related physiological and pathological aspects has not remained unscathed from the facets of nanotechnology. With each passing day investigators … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 144 publications
0
5
0
Order By: Relevance
“…The utilization of nanotechnology can enhance the quality of cryopreserved sperm and oocytes through the use of various nanomaterials, which provide protective barriers to prevent crystallization and cellular damage during the freezing process [ 122 ]. Bisla et al explore the application of nanoparticles in male fertility, specifically the ways in which metals, polymers, and carbon-based materials protect sperm, improve their quality, and reduce cell damage during the freezing-thawing process [ 123 ]. Additionally, Isaac et al investigate further the application of nanoparticles in human sperm cryopreservation and find that these particles can stabilize sperm cell membranes, reduce oxidative stress, and freezing-induced cell damage, thus improving sperm viability and motility [ 124 ].…”
Section: The Role Of Nanotechnology In the Prevention And Management ...mentioning
confidence: 99%
“…The utilization of nanotechnology can enhance the quality of cryopreserved sperm and oocytes through the use of various nanomaterials, which provide protective barriers to prevent crystallization and cellular damage during the freezing process [ 122 ]. Bisla et al explore the application of nanoparticles in male fertility, specifically the ways in which metals, polymers, and carbon-based materials protect sperm, improve their quality, and reduce cell damage during the freezing-thawing process [ 123 ]. Additionally, Isaac et al investigate further the application of nanoparticles in human sperm cryopreservation and find that these particles can stabilize sperm cell membranes, reduce oxidative stress, and freezing-induced cell damage, thus improving sperm viability and motility [ 124 ].…”
Section: The Role Of Nanotechnology In the Prevention And Management ...mentioning
confidence: 99%
“…It requires additional processing steps and may have limitations in terms of speed and accuracy depending on the target [15,88,91] Sperm sexing through CRISPR-Cas9 genetic tools Relatively high cost due to the need for gene editing reagents and equipment [96,97] Can be challenging to scale up [95,96] High potential for production efficiency if optimized properly. It offers precise genetic manipulation, but further development and validation are needed for commercial applications [94][95][96] Sperm sexing with magnetic nanoparticles Moderate to high cost due to the need for specialized nanoparticles and equipment [100] Can be scaled up, but may require optimization for large-scale implementation [113,114] Moderate to high impact on production efficiency. It enables efficient separation of sperm cells but requires additional steps and optimization for different species [100,114] Sperm sexing with Raman spectroscopy combined or not with digital holography…”
Section: Sexing Principle Cost Scalability Production Efficiencymentioning
confidence: 99%
“…It offers precise genetic manipulation, but further development and validation are needed for commercial applications [94][95][96] Sperm sexing with magnetic nanoparticles Moderate to high cost due to the need for specialized nanoparticles and equipment [100] Can be scaled up, but may require optimization for large-scale implementation [113,114] Moderate to high impact on production efficiency. It enables efficient separation of sperm cells but requires additional steps and optimization for different species [100,114] Sperm sexing with Raman spectroscopy combined or not with digital holography…”
Section: Sexing Principle Cost Scalability Production Efficiencymentioning
confidence: 99%
“…The word "nano" is a word of Greek origin and in the Greek language it is called "nanos".NanosIt means dwarf, The term Nano Refers to very subtle things a, And nanometres R or Nanometer (nm),that It is one billionth of a metre That is, one meter equals one billion nanometers(1 Nanometer = 10-9) (Al-Saadi, 2023). The philosophy of this technology Manufacture of materials whose dimensions are measured in nanometers, And This material has several unique properties due to a Her infinitesimals are small, she has capabilities apps Amazing (Kaddour & Othman, 2022), where Scientists believe Nanoparticles(NPs)The nanostructured materials originated during the Big Bang process of meteorites that led to the formation of the universe and the Earth (Barhoum et al, 2022), Substance use indicated then no first time by Richard P. Feynman1959 in his lecture entitled (Hussein & Aldujaili, 2022)There is plenty of room at the bottom And in 1974 the Japanese scientist formulated Norio Taniguchiterm Nanotechnology (NT) (Bisla et al, 2022). Nanotechnology has reached almost every sector and has amazed the world by offering many potential applications in this sectorT,Since nanostructured materials are known for their unique physical and chemical properties and improved performance and are therefore preferred over their macro structured counterparts, (Chausali et al, 2022).…”
Section: Review Of References Nanotechnologymentioning
confidence: 99%
“…A scanning electron microscope is one of the best microscopes To study the surface quality, where Cross section of the nanostructurejresult appeared the photomicrograph for FESEM on about facilitator, An image was usedSEM to determine the shape and size of the biosynthetic nanoparticles, where they were found in different sizes and using different magnification powers, and the results were examined, as the electronic scanning of SeNPs showed that the basic shape of the particles is a rod and the particles were homogeneous in sizeand figTo some extent ,program was usedImage JTo measure the diameters of nanoparticles were the extentTheir diameters range between nmAs in Figure (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). The results of these dimensions show convergence with what has been achieved (Chhabria & Desai, 2016).Where she wasSeNpsincluded in their studiesrodAnd the dimensions of its diameters are 59_+4.…”
Section: Characterization Of Nanoparticles Field Emission Scanning El...mentioning
confidence: 99%